The e-learning survey analysis in Universitas Sarjanawiyata Tamansiswa: Should it be improved? - Widowati Pusporini; Devi Septiani; Susanti Susanti (Research and Social Study Institute, 2021)
E-learning is not a new issue in education. This research aims to analyze the readiness of early-semester students to implement e-learning at Universitas Sarjanawiyata Tamansiswa. The readiness of students in facing lectures in this pandemic period is considered to be an important issue in the implementation of online lectures. This study is qualitative research using survey methods to describe students' responses to university e-learning in an even semester. This research was conducted by disseminating survey instruments using the RASE model to students using SIPEDAR (university e-learning platform) and academic portal. The research subjects were students in the Educational Research and Evaluation Post-Graduate program and undergraduate science education program in Universitas Sajanawiyata Tamansiswa. The finding of this study stated that Students' responses on e-learning resources had an average of 3.29 (excellent). The students' responses to the activity features in e-learning reached an average of 3.25 (excellent). The student's response to the support features in e-learning with an average of 3.16 (excellent), and The student's response indicator on evaluation in e-learning by 3.21 (excellent).